2018
DOI: 10.1038/s41598-018-22057-7
|View full text |Cite
|
Sign up to set email alerts
|

Human protective response induced by meningococcus B vaccine is mediated by the synergy of multiple bactericidal epitopes

Abstract: 4CMenB is the first broad coverage vaccine for the prevention of invasive meningococcal disease caused by serogroup B strains. To gain a comprehensive picture of the antibody response induced upon 4CMenB vaccination and to obtain relevant translational information directly from human studies, we have isolated a panel of human monoclonal antibodies from adult vaccinees. Based on the Ig-gene sequence of the variable region, 37 antigen-specific monoclonal antibodies were identified and produced as recombinant Fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
114
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(126 citation statements)
references
References 50 publications
8
114
0
Order By: Relevance
“…Another possible explanation is species-specific differences in C1q engagement by 1E6. Our results are consistent with prior studies with anti-fHbp mAbs (murine or human), where human complement-mediated bactericidal activity was observed only if the mAb blocked fH-binding or was used in combination with other mAbs (29, 30, 41). Previous studies demonstrated that the quantity of fHbp present on the bacterial surface varies between isolates and in the strains used, MC58, M08-0240104, and UK320 the concentration of fHbp was determined to be 2900 (fHbp v1), 9390 (fHbp v2), and 1111(fHbp v3) molecules for cells, respectively (57).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Another possible explanation is species-specific differences in C1q engagement by 1E6. Our results are consistent with prior studies with anti-fHbp mAbs (murine or human), where human complement-mediated bactericidal activity was observed only if the mAb blocked fH-binding or was used in combination with other mAbs (29, 30, 41). Previous studies demonstrated that the quantity of fHbp present on the bacterial surface varies between isolates and in the strains used, MC58, M08-0240104, and UK320 the concentration of fHbp was determined to be 2900 (fHbp v1), 9390 (fHbp v2), and 1111(fHbp v3) molecules for cells, respectively (57).…”
Section: Discussionsupporting
confidence: 92%
“…Giuliani et al (41) restricted the epitope localization of 1 crossreactive anti-fHbp mAb 1G3 to short fragments of fHbp v1 by hydrogen-deuterium exchange–MS, whereas López-Sagaseta et al (18) were able to fully characterize at high resolution, by X-ray crystallography, the first human antibody, the 1A12, identifying the epitope on fHbp v1. Fab 1A12 targets exclusively the C-terminal β-barrel, whereas the Fab 1E6 mainly binds the N-terminal region on the opposite side compared to the binding site for hfH ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations